Resources of the workers of small and medium business and their well-being in the labor market - Yu Yu Chilipenok; O S Osipova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article presents the results of the study aimed to describe the employee of small and medium business as a subject of the contemporary Russian social and labor relations in terms of his resource endowments. From the theoretical point of view, the study was conducted within the resource-based approach: the main resources of small and medium business employees, their behavior in the labor market as depending on the resource supply were analyzed on the data of the Russian monitoring of the economic situation and the health of the population (RLMS) of the National Research University “Higher School of Economics”. The employees’ well-being in the labor market was measured by the fear to lose one’s jobs, and confidence in the ability and the desire to find a new job. Based on the empirical data the authors identify average, normal levels of resource endowments, and the features of the subject of social and labor relations in the light of particular levels of different resources supply. The authors note the low economic security of small and medium business employees as a reason for the financial factor to have a decisive influence on the behavior of this category of workers in the labor market. There also conclusions about the importance of information and innovative resource and workers’ health to realize their independent position in the labor market and get ready for the labor mobility.